Essentials of integrated anatomy : objective practical questions and answers - Maung, Maung Nyo; Nan, Ommar. (UNIMAS Publisher, 2010)
This book is prepared to help the students studying in Phase 1 part of the medical curriculum at FMHS, UNIMAS, gain basic anatomical knowledge that is required for physical examination and diagnosis of diseases. The format of the book reflects the Objectively Structured Practical Examination (OSPE) conducted in our faculty (FMHS, UNIMAS) where the basic sciences are integrated with the clinical sciences through the Problem-Based Learning (PBL) approach. This format helps the students to learn not only gross anatomy, but also other branches of anatomy namely histology, embryology and neuroanatomy in an integrated and applied manner.